Baricitinib in patients admitted to hospital with COVID-19 (RECOVERY): a randomised, controlled, open-label, platform trial and updated meta-analysis - RECOVERY Collaborative Group; Horby, P; Emberson, J; Mafham, M; Peto, L; Campbell, M; Pessoa-Amorim, G; Spata, E; Staplin, N; Day, J; Juszczak, E; Knight, M; et al. (Elsevier, 2022)
Background: We aimed to evaluate the use of baricitinib, a Janus kinase (JAK) 1–2 inhibitor, for the treatment of patients admitted to hospital with COVID-19.